2010
DOI: 10.1097/pas.0b013e3181f0a873
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Clinicopathologic Features and Prognostic Factors in Hepatoid Adenocarcinoma of the Stomach

Abstract: HAS had different clinicopathologic features and prognosis from non-HAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
62
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(71 citation statements)
references
References 16 publications
9
62
0
Order By: Relevance
“…[12,13] Our study revealed a similar incidence rate (0.22%) with a high incidence of metastasis. According to a previously published report, [14] patients with GHA have an average age of 63.5 years, are predominantly male (2.32:1), have tumors mainly located at the antrum, and tend to have high levels of AFP.…”
Section: Discussionsupporting
confidence: 54%
“…[12,13] Our study revealed a similar incidence rate (0.22%) with a high incidence of metastasis. According to a previously published report, [14] patients with GHA have an average age of 63.5 years, are predominantly male (2.32:1), have tumors mainly located at the antrum, and tend to have high levels of AFP.…”
Section: Discussionsupporting
confidence: 54%
“…Previous studies have reported that HAS frequently occurred with liver metastasis and exhibited a shorter interval between gastrectomy and liver metastasis than that of CGC, leading to a poorer prognosis (17,18). As reported by Liu et al, the one-, three-and five-year survival rates of HAS were 30, 13 and 9%, respectively, compared with 95, 57 and 38%, respectively in the CGC group (19).…”
Section: A B C Dsupporting
confidence: 56%
“…The lower one third of the stomach is most common location for afpgc or has, in the range 40%-61.5% 3,6,[11][12][13]16 . Our observation was similar.…”
Section: Discussionmentioning
confidence: 99%
“…Liver metastasis (14.3%-75.6%) is one of the main features of afpgc or hepatoid adenocarcinoma of the stomach (has) [12][13][14]16 . In our series, 16 patients (27.6%) in the afpgc group were found to have liver metastasis during follow-up.…”
Section: Discussionmentioning
confidence: 99%